Characteristics of defect modes in side-coupled and mutually coupled microresonator arrays - Tobing, Landobasa Yosef Mario A. L. (2013)
We present both theoretically and experimentally the existence of defect modes in side-coupled and mutually coupled microresonator arrays. The qualitative difference between the two types of defect modes is investigated. The Qfactor of both defect modes for varying defect sizes is characterized, and an enhancement of ∼30×relative to individual loaded resonators is demonstrated. The defect modes are then compared with coupled resonator–induced transparency (CRIT), indicating that the defect modes based on side-coupled microresonator arrays are actually the extension of the CRIT resonance in two-resonator structures.